A Prominent Role of Interleukin-18 in Acetaminophen-Induced Liver Injury Advocates Its Blockage for Therapy of Hepatic Necroinflammation - Bachmann, Malte; Pfeilschifter, Josef; Mühl, Heiko (Frontiers in Immunology, 2018)
Acetaminophen (paracetamol, N-acetyl-p-aminophenol, APAP)-induced acute liver injury (ALI) not only remains a persistent clinical challenge but likewise stands out as well-characterized paradigmatic model of drug-induced liver damage. APAP intoxication associates with robust hepatic necroinflammation the role of which remains elusive with pathogenic but also pro-regenerative/-resolving functions being ascribed to leukocyte activation. Here, we shine a light on and put forward a unique role of the interleukin (IL)-1 family member IL-18 in experimental APAP-induced ALI. Indeed, amelioration of disease as previously observed in IL-18 deficient mice was further substantiated herein by application of the IL-18 opponent IL-18 binding protein (IL-18BPd:Fc) to wild-type mice. Data altogether emphasize crucial pathological action of this cytokine in APAP toxicity. Adding recombinant IL-22 to IL-18BP:Fc further enhanced protection from liver injury. In contrast to IL-18, the role of prototypic pro-inflammatory IL-1 and tumor necrosis factor-a is controversially discussed with lack of effects or even protective action being repeatedly reported. A prominent detrimental function for IL-18 in APAP-induced ALI as proposed herein should relate to its pivotal role for hepatic expression of interferon-g and Fas ligand, both of which aggravate APAP toxicity. As IL-18 serum levels increase in patients after APAP overdosing, targeting IL-18 may evolve as novel therapeutic option in those hard-to-treat patients where standard therapy with N-acetylcysteine is unsuccessful. Being a paradigmatic experimental model of ALI, current knowledge on ill-fated properties of IL-18 in APAP intoxication likewise emphasizes the potential of this cytokine to serve as therapeutic target in other entities of inflammatory liver diseases.